1988
DOI: 10.1126/science.3201258
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Hemispheric Specialization in Monkeys

Abstract: Twenty-five split-brain monkeys were taught to discriminate two types of visual stimuli that engage lateralized cerebral processing in human subjects. Differential lateralization for the two kinds of discriminations was found; the left hemisphere was better at distinguishing between tilted lines and the right hemisphere was better at discriminating faces. These results indicate that lateralization of cognitive processing appeared in primates independently of language or handedness. In addition, cerebral latera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
89
2

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(106 citation statements)
references
References 8 publications
15
89
2
Order By: Relevance
“…Hemispheric asymmetry has not been re ported in previous 2-DG memory studies, though it would have been missed in most because of the proce dures used, e.g., the use of a visually deafferented hemi sphere as control (Macko et aI., 1982;Macko and Mish kin, 1985) or the measurements done in one hemisphere only (Friedman and Goldman-Rakic, 1988). Interpreta tion for this new observation can only be speCUlative at this stage, but would be in line with growing evidence for hemispheric specialization in the nonhuman primate (Hamilton and Vermeire, 1988;Fagot and Deruelle, 1997;Gannon et aI., 1998). Preferential involvement of the left hemisphere for visual analytic processes has been reported both in man (Kawashima et aI., 1998;Vanden berghe et aI., 1996;Sergent et aI., 1992;Shen et aI., 1999) and in the nonhuman primate (Fagot and Deruelle, 1997;Vermeire et aI., 1998), which may have relevance to our finding.…”
Section: Discussionmentioning
confidence: 78%
“…Hemispheric asymmetry has not been re ported in previous 2-DG memory studies, though it would have been missed in most because of the proce dures used, e.g., the use of a visually deafferented hemi sphere as control (Macko et aI., 1982;Macko and Mish kin, 1985) or the measurements done in one hemisphere only (Friedman and Goldman-Rakic, 1988). Interpreta tion for this new observation can only be speCUlative at this stage, but would be in line with growing evidence for hemispheric specialization in the nonhuman primate (Hamilton and Vermeire, 1988;Fagot and Deruelle, 1997;Gannon et aI., 1998). Preferential involvement of the left hemisphere for visual analytic processes has been reported both in man (Kawashima et aI., 1998;Vanden berghe et aI., 1996;Sergent et aI., 1992;Shen et aI., 1999) and in the nonhuman primate (Fagot and Deruelle, 1997;Vermeire et aI., 1998), which may have relevance to our finding.…”
Section: Discussionmentioning
confidence: 78%
“…An often-cited functional lateralization in the brain concerns the processing of faces, which activates ventral occipital areas in the right hemisphere 95 . This functional asymmetry is heritable 96 , is stable within individuals 97 and is also present in macaque monkeys 98 . As such, it can be thought of as a fundamental lateralization of the brain.…”
Section: Cerebral Lateralizationmentioning
confidence: 99%
“…In marmosets, rhesus monkeys and chimpanzees, species-specific facial expressions are expressed more intensely on the left compared to the right side of the face (Fernandez-Carriba, Loches, & Hopkins, 2002;Hook-Costigan & Rogers, 1998;Hauser, 1993). It has also been reported that split-brain monkeys discriminate species-specific facial expression better with the right compared to the left hemisphere (Hamilton & Vermeire, 1988;Vermeire & Hamilton, 1998) and prefer to look at conspecifics with the right compared to left eye (Ifune, Vermeire, & Hamilton, 1984; see also Rogers, Ward, & Stafford, 1994 for visual preference results in bush babies). Physiologically, differences between the EEG power functions of the left and right frontal cortex predicts approach-avoidance in rhesus monkeys (Kalin, Larson, Shelton, & Davidson, 1998) as well as lateralized responses to anxiety medications (Davidson, Kalin, & Shelton, 1992).…”
mentioning
confidence: 97%